Evolution of Brassica rapa L. var. rapa volatile composition by HS-SPME and GC/IT-MS. - Taveira, M. (2011)
Brassica rapa var. rapa L. (turnip) is highly appreciated and consumed by human. In this work, the volatile profile of B. rapa var. rapa was studied during the maturation process. The volatiles of seeds, sprouts with 6 and 9 days, and adult plant were determined using headspace solid-phase microextraction (HS-SPME) combined with gas chromatography/ion trap-mass spectrometry (GC/IT-MS). Several constituents, including alcohols, aldehydes, esters, ketones, norisoprenoids, nitrogen and sulphur compounds were characterized, totalizing 64 compounds. Isothiocyanates are the main volatiles in all matrices, being 3-butenyl isothiocyanate the major compound. Qualitative and quantitative differences were found among the analysed materials. Nitrogen and sulphur compounds decreased during the maturation process, while terpenes, aldehydes, norisoprenoids and ester compounds were present in higher amounts during germination, especially in sprouts with 9 days of development.